Examining the Causal Linkages among Domestic Investment, FDI, Trade, Interest Rate and Economic Growth in ASEAN-5 Countries - TAN, Bee Wah; TANG, Chor Foon (International Journal of Economics and Financial Issues, 2016)
The aim of this study is to empirically analyse the linkages among domestic investment, FDI, trade, interest rate and economic growth in the ASEAN-5 regions in the period 1970-2012. The Johansen-Juselius cointegration approach is applied to examine the long-run relationship and the Granger causality approach is applied to evaluate the causal linkages among the variables. The results confirm the existence of long-term causal links between domestic investment and FDI for the ASEAN-5. This means that collaboration of domestic and foreign investors is essential as the development of domestic firms contributes to further participation by multinational investors. We also reveal that domestic investment and FDI are growth enhancing and their impact is felt in both short- and long-run in the majority of the ASEAN-5 markets, indicating that these three variables are interrelated since they could be attracted to the growing economies. Thus, economic policies that aim at improving and promoting both local and foreign enterprises are indeed necessary in stimulating economic growth in the ASEAN-5 nations. Keywords: ASEAN-5; Causality; Cointegration; Domestic Investment; FDI; Economic Growth JEL Classifications: C32; O11